Politics of the Possible gender mainstreaming and organisational change:experiences from the field - Maitrayee, Mukhopadhyay (Amsterdam KIT Publishers, 2006)
What actually happens to organizations during gender and organization change endeavors? This book takes an in-depth look at the experience of seven Novib partner organizations in the Middle East and South Asia who undertook the challenge of the Gender Focus Programme. It recounts their analysis of their organization, and the route they chose to follow. The book presents field experiences of managing the politically sensitive agenda of promoting gender equality in the NGOs and negotiating the contradictions between using Organizational Development tools and promoting gender equality.
Includes bibliographies
Keywords: Gender